Catalytic ethanolysis of Xilinguole lignite over layered and mesoporous metal oxide composites to platform chemicals. (1st March 2021) - Li, Zhan-Ku; Wang, Hai-Tao; Yan, Hong-Lei; Yan, Jing-Chong; Lei, Zhi-Ping; Ren, Shi-Biao; Wang, Zhi-Cai; Kang, Shi-Gang; Shui, Heng-Fu
Highlights: Catalytic ethanolysis of Xilinguole lignite with MMgAlO x was conducted. The MMgAlO x have layered and mesoporous structures with tunable acidity/basicity. Yields of ethanol-soluble portions can be dramatically enhanced by the catalysts. The catalysts can preferably reserve the aromatic rings to produce arenes and phenols. Platform chemicals can be controlled by changing the catalysts. Abstract: Ethanolysis is an efficient approach for converting lignites into chemicals under mild conditions. However, yield of soluble portion from lignite ethanolysis is limited and product distribution cannot be well regulated. In this paper, a series of catalysts (MMgAlO x, M = Cu, Zn, Co, Ni) were prepared by a coprecipitation method. The catalysts were characterized by X-ray powder diffraction, high resolution transmission electron microscope, N2 physisorption, and CO2 - and NH3 -temperature-programed desorption. The results show that the catalysts have layered and mesoporous structures with tunable acidity/basicity. Catalytic ethanolysis of Xilinguole lignite was performed and the resulting ethanol-soluble portions (ESPs) were analyzed with a Fourier transform infrared spectrometer, thermogravimetric analyzer, and gas chromatograph/mass spectrometer. The results suggest that except NiMgAlO x, other catalysts significantly increased the yields of the ESPs, especially CuMgAlO x and ZnMgAlO x, which is probably related to the amount of H2 produced from ethanol. Four major platform chemicals, i.e., arenes, phenols, alcohols, and esters, can be produced via the catalytic ethanolysis. The catalysts have high ethanolysis activity and low hydrogenation ability and therefore aromatic rings can be reserved. Distribution of the platform chemicals could be tuned by altering the catalysts. In addition, possible pathways on the catalytic ethanolysis were proposed.